2021
DOI: 10.1111/pan.14131
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia for children with complete trisomy 18 (Edwards syndrome): A cohort review of 84 anesthesia encounters in nine patients

Abstract: Background: Trisomy 18 or Edwards syndrome is the second most common ane

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Higher risk procedures include scoliosis repair surgery and cardiac surgery. Notably, most observed procedures were performed during infancy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher risk procedures include scoliosis repair surgery and cardiac surgery. Notably, most observed procedures were performed during infancy [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the large cohort review encompassing 11 patients with trisomy 18 did include two patients, who were 16 and 11 years of age, respectively; combined, these two patients received a total of 31 anesthetics with complications related to difficult intubation, laryngospasm, and bradycardia. Other anesthetic complications cited in the review included difficult bag-valve-mask ventilation, difficult IV access and cardiac events necessitating resuscitation, which included cardiopulmonary reanimation (CPR) in younger patients [ 3 ]. Further, a recent retrospective review of airway management of trisomy 18 patients found that there was a decreased risk of difficult intubation in patients older than 6 years of age compared with their younger counterparts [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trisomy 18 is a common autosomal chromosomal abnormality characterized by malformations throughout the body and occurs in approximately 1/3,600 to 1/10,000 live births [ 1 ]. Approximately 50% of newborns with trisomy 18 expire within the first week of life, with only 10% reaching their first birthday [ 2 ]. Children with trisomy 18 may require gastrointestinal, airway, or cardiac surgery during infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Children with trisomy 18 may require gastrointestinal, airway, or cardiac surgery during infancy. The abnormal airway anatomy, including micrognathia, high-arched palate, and short neck makes mask ventilation, and tracheal intubation challenging [2]. Supraglottic airways (SGAs) play an important role in difficult airway management in both adults and children [3].…”
Section: Introductionmentioning
confidence: 99%
“…2e4 Airway management is thought to be challenging because of micrognathia/retrognathia and restricted mouth opening, which can lead to difficulties with mask ventilation and tracheal intubation, as reported in a single case series. 5 Larger studies comprehensively examining airway management in children with trisomy 18, including incidence and risk factors of difficult airway, specific techniques used, and related complications, have not been published.…”
mentioning
confidence: 99%